CleanServs: clean services for a more sustainable world. Issue 4 (28th October 2014) - Wolfson, Adi; Tavor, Dorith; Mark, Shlomo
Abstract : Purpose: – The paper aims to describe a novel framework for service design to achieve the overall goal of sustainability and to characterize it while exploring the benefit of doing so for both sustainability and service. This novel framework also proposes new opportunities for sustainability-oriented innovation. Design/methodology/approach: – The paper presents a novel approach to design and implement services that will lead to a reduction in the production of goods and will offer alternatives that will reduce whatever production process is involved in its creation, i.e. clean service – CleanServ. Findings: – The authors' findings suggest that a CleanServ is a service that is competitive with, if not superior to, its conventional tangible or intangible counterparts and one that reduces the use of natural resources and cuts or eliminates emissions and wastes. CleanServs can be categorized into five different groups based on their fundamental contribution to sustainability: prevention, reduction, replacement, efficiency and offset. While the service sector continuous to grow in size and importance, CleanServs will play a key role in improving the sustainability of our society and in preserving the environment. Practical implications: – The CleanServ concept offers a new framework and novel opportunities for sustainability-oriented innovation in the service sector. Implementing CleanServs will enable services to be imbued with sustainability and will promote the exchange of the production of goods with the delivery of services that will supply the same solution more sustainably. Social implications: – CleanServs are expected to change how we consume both products and services and will, therefore, promote a more rational use of natural resources and will reduce the discharge of pollution to the environment. Implementation of the CleanServ concept will, thus, advance the current state of the art in sustainable development and improve quality of life on a global scale. Originality/value: – This paper presents a novel approach and a framework that conceptualizes clean services, which we term CleanServs, while exploring the benefit of doing so, both for sustainability and for service science.